1996
DOI: 10.1046/j.1365-2958.1996.376903.x
|View full text |Cite
|
Sign up to set email alerts
|

A dual role for the Bacillus subtilis glpD leader and the GlpP protein in the regulated expression of glpD: antitermination and control of mRNA stability

Abstract: The Bacillus subtilis glpD gene encodes glycerol-3-phosphate dehydrogenase. This gene is preceded by a leader region containing an inverted repeat which acts as a transcription terminator. Expression of glpD is controlled by antitermination of transcription at the inverted repeat. Antitermination is effected by the glpP gene product in conjunction with glycerol-3-phosphate and, consequently, GlpP mutants fail to grow on glycerol as a sole carbon and energy source. We have isolated a number of glycerol-positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0
2

Year Published

1997
1997
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 27 publications
0
46
0
2
Order By: Relevance
“…This is a known mechanism for stabilizing or destabilizing transcripts. For example, B. subtilis glpD mRNA can be stabilized by the GlpP antiterminator protein (Glatz et al, 1996) and in E. coli, the ompA and glgC transcripts are destabilized by the Hfq and CsrA proteins, respectively (Vytvytska et al, 1998, Liu & Romeo, 1997. Finally, we wish to point out that there are striking sequence similarities between the sequence around the aprE RBS and that of a polypurine-rich sequence in bacteriophage SP82 which functions as a 5h stabilizer in B. subtilis (Hue et al, 1995).…”
Section: Discussionmentioning
confidence: 98%
“…This is a known mechanism for stabilizing or destabilizing transcripts. For example, B. subtilis glpD mRNA can be stabilized by the GlpP antiterminator protein (Glatz et al, 1996) and in E. coli, the ompA and glgC transcripts are destabilized by the Hfq and CsrA proteins, respectively (Vytvytska et al, 1998, Liu & Romeo, 1997. Finally, we wish to point out that there are striking sequence similarities between the sequence around the aprE RBS and that of a polypurine-rich sequence in bacteriophage SP82 which functions as a 5h stabilizer in B. subtilis (Hue et al, 1995).…”
Section: Discussionmentioning
confidence: 98%
“…Among the B. subtilis mRNAs targeted by the RppH-dependent pathway is the 2.2-kb transcript of the yhxA-glpP operon, which encodes a transcription antiterminator (GlpP) important for regulating the synthesis of glycerol-3-phosphate dehydrogenase (11). The lifetime of this transcript can be prolonged in B. subtilis by deleting the rppH gene, by depleting the 5′-exonuclease subunit of RNase J, or by adding a 5′-terminal stem loop, an RNA modification that prevents 5′ attack by both RppH (7) and RNase J (4).…”
mentioning
confidence: 99%
“…When the wild-type glpP gene is introduced into these strains the glpD mRNA is stabilized. Introduction of glpP also restores glucose repression indicating that it is mediated by the GlpP protein (Glatz et al, 1996).…”
Section: The Glp Regulon Of B Subtilismentioning
confidence: 94%
“…For the glpD operon it has been shown that full-length transcripts are obtained under inducing conditions, while under non-inducing conditions, the transcripts terminate at nucleotides in the downstream stem of the terminator (Holmberg and Rutberg, 1991;. Point mutations and deletions within the glpD terminator sequence lead to constitutive, GlpP-and G3P-independent expression of glpD (Glatz et al, 1996). They also result in glucose-repression-insensitive expression of glpD.…”
Section: The Glp Regulon Of B Subtilismentioning
confidence: 99%